The study of the Ca dispersion in coke and effect of Ca and Fe on the coke reactivity using the sole heated oven cokes. (15th March 2020) - Jayasekara, Apsara S.; Monaghan, Brian J.; Longbottom, Raymond J.; Mahoney, Merrick R.; Hockings, Kim
Highlights: Ca dispersion in coke was studied using sole heated oven cokes. Ca was found to be dispersed and reacted with minerals. Effect of Ca and Fe on coke reactivity was tested using sole heated oven cokes. Reactivities of Ca and Fe added cokes increased with increasing Ca and Fe content. Abstract: The dispersion of Ca and the effect of Ca and Fe on the coke reactivity were studied using Sole Heated Oven (SHO) cokes prepared from washed Australian coal samples and added minerals, lime and magnetite. It was observed that the Ca from added lime were dispersed throughout the coke, with a smaller particle size, similar to the dispersion of Ca in the coke analogue, low ranked coals and coke prepared from low ranked coals. Ca had also reacted with minerals from the parent coals to form complex Ca-Al/Si oxy sulfides. The effects of Ca and Fe content on the coke reactivity with CO2 were studied using a TGA at 1373 K by adding varying amounts of lime and magnetite. Both lime and magnetite additions increased coke reactivity. It was found that the reactivity of lime added SHO cokes increased with increasing Ca content in the cokes. The reactivity of Fe containing SHO cokes increased with increasing Fe content in the cokes. However, the Ca addition had a much larger effect on coke reactivity, nearly doubling the coke reactivity compared to the Fe addition. The effect of the Ca addition on reactivity is likely to be accentuated by the dispersion of small Ca particles through the coke, which increased the mineral-carbon contact area.